Calculation and Improvement of Complex Mechanical Properties of the Mega Arch Dam under Multiple Loads Based on Finite Element Methods - Chenghua Fu; Hongbo Zhou; Yanfang Pan (Complexity)
Researches on dynamic responses of the arch dam under seismic waves were not systematic and perfect enough in published papers. They rarely proposed measures to improve the antiseismic performance of the arch dam under seismic waves. Based on the finite element method, this paper completed a systematic and perfect research on stress and damage of the arch dam under seismic waves and proposed an effective measure to improve the antiseismic performance. The computed results of the improved arch dam were compared with the original one. Results proved that improved effects are obvious. In addition, damage stabilization value of the improved arch dam was 0.47, while the original one was 0.13. Obviously, the safety of the improved arch dam under the same loads was higher. Damage of the improved arch dam was increased by stages. It took about 3 s from zero damage to the complete damage, while the time was about only 1.3 s for the original one. Obviously, the antidamage capability of the improved arch dam was better. The improved measure proposed in this paper is very effective. This paper provides one reference for studying and improving the antiseismic performance of the arch dam.